INFLUENCE OF AGE ON THE SUSCEPTIBILITY OF PIGLETS TO ESCHERICHIA COLI O138:F18 - Sugiharto, S.; Lauridsen, C. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The ex vivo and in vivo studies were undertaken to examine age-effect on the susceptibility of pigsto E. coli F18-diarrhea. The ex vivo experiment was conducted with 2 and 4 weeks old pigs based on theporcine intestinal organ culture (PIOC) model. The in vivo experiment was performed with 2 and 3weeks old pigs fed milk replacer and inoculated with E. coli F18. E. coli F18 inoculation to the intestinalcultures resulted in higher (P<0.01) counts of E. coli associated to the intestinal tissue, but suchdifference was not observed between the 2 and 4 weeks old pigs. Faecal dry matter (DM) decreased(P=0.01), whereas the proportion of pigs with diarrhea and faecal haemolytic E. coli counts increased(P<0.05) following inoculation, however, the difference between the ages was not observed in the invivo study. The interaction (P=0.01) between age and sampling day was observed for the number of totalwhite blood cells (WBC). The proportion of neutrophils decreased (P=0.01), whereas the lymphocytes,red blood cells (RBC), hemoglobin (Hb) and hematocrit (Hct) increased (P<0.01) after inoculation, butthe differences between age groups were not observed regarding these variables. In conclusion, age (2versus 3 or 4 weeks) did not influence the susceptibility of piglet to E. coli F18-diarrhea.